Antibiotic induced liver injury: what about children?. (October 2013) - Serranti, Daniele; Montagnani, Carlotta; Indolfi, Giuseppe; Chiappini, Elena; Galli, Luisa; Martino, Maurizio de
Abstract : Antimicrobial agents are important causes of drug-induced liver injury. They are responsible for about 45% of cases of drug hepatotoxicity. Hepatic damage mechanisms are intrinsic or idiosyncratic. Usually, antibiotics are responsible for idiosyncratic toxicity. This review summarizes the rate of incidence and clinical features of hepatotoxicity due to antibiotics and chemotherapics, with particular attention to data regarding paediatric population. Liver injury features have been systematically evaluated for the most commonly administered antibiotics and chemotherapics in adults, even though there is little information about other widely used compounds, as cephalosporine or clarithromycin, and about antibiotics active against multi-resistant bacteria, as carbapenems, vancomycin, clindamycin, and linezolid. By contrast, there is an abundance of case reports in paediatrics, but very few structured studies have been carried out in children. Children are an important class of antibiotic users, with specific metabolic characteristics, so more studies on them should be carried out.